A review of heat transfer and thermal management methods for temperature gradient reduction in solid oxide fuel cell (SOFC) stacks. (15th December 2020) - Zeng, Zezhi; Qian, Yuping; Zhang, Yangjun; Hao, Changkun; Dan, Dan; Zhuge, Weilin
Highlights: Heat transfer mechanisms in solid oxide fuel cells (SOFC) are discussed. Values of temperature gradient of SOFC in literature are summarized. Thermal management methods of SOFC are reviewed and compared. Suggestions for future studies of SOFC thermal management are provided. Abstract: Solid oxide fuel cell (SOFC) stacks are promising power generation devices due to their high efficiency and flexible fuel capability. Recent application of SOFC stacks has shifted from stationary electricity generation into powering vehicles and airplanes. The start-up process of compact SOFC stacks for mobile power systems requires a rapid temperature rise from 20 °C to approximately 800 °C. Effective thermal management systems are necessary for the stable start-up process as well as stable operations of SOFC stacks. This paper presents a detailed review on the heat transfer studies of SOFC and the associated thermal management methods. Previous studies have indicated that the temperature gradient in the SOFC could lead to delamination and cracks in the electrolyte and electrode. Thus, we listed the temperature gradient for different types of SOFC and summarized the commonly used thermal management methods for temperature gradient reduction in SOFC stacks, such as designing proper gas channels, using effective flow arrangements, integrating heat pipes into interconnects, and adjusting fuel compositions. The suggestions for future studies related to thermal management of SOFC are also provided. This review helps improve our understanding of the heat transfer mechanisms in SOFC and inspire researchers to design effective thermal management systems for SOFC stacks.